Taylor$1 (Bs 7th Teaching and Learning Conference 2014 Proceedingss Holistic Education: Enacting Change - Tang, Siew Fun.; Logonnathan, Loshinikarasi; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
These conference proceedings showcase a rich and practical exchange of approaches and vital evidence-based practices taking place around the world. They clarify the complex challenges involved in bringing about a holistic educational environment in schools and institutes of higher learning that fosters greater understanding, and offer valuable insights on how to avoid the pitfalls that come with rolling out holistic approaches to education. To do so, the proceedings focus on the subthemes Support and Development, Mobility and Diversity, and Networking and Collaboration in Holistic Education.
Part I Introduction -- 1 Whole Teachers: An Inquiry into Krishnamurti's Educational Philosophy -- Part II Mobility & Diversity -- 2 Project-based learning for building work and life skills in line with Taylor's Graduate capabilities -- 3 Inside and Out: Malaysian and non-Malaysian tropes, the Comparative Approach, and the Works of Tunku Halim and James Wan -- 4 A sociocultural perspective of factors influencing academic writing from school to postsecondary education -- 5 Emotional intelligence and academic achievement: A study among students of a private university in Malaysia -- 6 Cross cultural challenges and synergies working in an international collaboration project -- 7 A study on factors affecting user's interest in using social networking sites -- 8 Academic performance and perceptions of female students in Civil Engineering -- 9 A study on academic performance of International students -- 10 Factors that affect students' mental health: A study at Taylor's University School of Hospitality, Tourism and Culinary Arts Final Year students -- 11 Understanding student's acceptance and adoption of Web 2.0 Interactive Edu tools -- 12 "Initially, it was Meticulous, but Now I Prefer Online": A case study on the implementation of e-Examination in Taylor's University -- Part III Supporting & Development -- 13 Are students pursuing higher education aware of personal development planning and its importance? A pilot study at Taylor's University -- 14 Quantitative assessment of Students Cognitive, Psychomotor, and Affective Learning Skills for Taylor's University Engineering Programmes -- 15 Constructivist Learning Environments and Academic Achievement: A study of Iranian TEFL Students -- 16 The impact of the Physical learning spaces on Learning Process -- 17 Preliminary analysis of learning effectiveness between the MIB and non MIB User -- 18 Effects of spreadsheet towards mathematics learners' problem solving abilities -- 19 End of Semester Objective Structured Clinical Examinations in Taylor's University School of Medicine Clinical School: Review of overall reliability and the domains assessed -- 20 Developing a new method of mobile learning among distance learners in a public university -- 21 The importance and implementation of technology for Diploma Accounting students in the University of Johannesburg -- 22 CDIO attainment for Taylor's Undergraduate Chemical Engineering Program -- 23 E-learning Pilot Project: Challenges and initiatives in the implementation of E-Learning in the Malaysian Studies Module at Taylor's University -- 24 Holistic Education and Teacher Professional Learning in the 21st Century -- 25 YouTube and English Literature: Beyond the Chalk and Board -- 26 An empirical study of determinants of teachers' effectiveness in Higher Education Institutions in Pakistan -- 27 The impact of Holistic Education Approaches on First-Year Experience of Business Undergraduates: Promotion interactive and creative learning environments -- 28 Learning enhancement through blended learning environment via learning management system, social learning platform and video: A case study at Taylor's University -- 29 The perceptions of MOOC among Learners Based on Activity Theory -- 30 What have students gained from college experience -- 31 2D Side-Scrolling Game: Applying motivation and Digital Game Based Learning (DBGL) in English Learning -- 32 A survey analysis: Students interest in Simplification Game Development Tools for Creative Learning -- 33 Taylor's University Lakeside Campus: Application and Effectiveness in e-Learning Tools for Students Learning Activities -- 34 Design Model for Integrating Learning Activity Management System (LAMS), Massive Open Online Courses (MOOC) and Flipped Classroom in Taylor's Integrated Moodle e-Learning System (TIMeS) -- 35 Holistic assessment: Creating assessment with students -- 36 Outcomes base approach for a new Pharmacoinformatics Course for Bachelor of Pharmacy Programme -- 37 X-Space: A way forward? The perception of Taylor's University students' on collaborative learning spaces -- 38 Practical tips to facilitate CO:PO Mapping and Documentation -- 39 Blended learning in engineering education: Curriculum redesign and development -- 40 Education quality and learning outcomes in higher education institutions in Pakistan -- 41 Can future teachers ready to be the ICT change agents? -- 42 The influence of Mobile Learning on Learner's Absorptive Capacity: A case of Bring Your Own Device (BYOD) Learning Environment -- 43 The impact of Digital Literacy Training on learning performance of University students in a Problem-based Learning Environment -- 44 Holistic Education in a Preparatory High School: An innovative program to prepare students for the future -- 45 Students' patterns and level of social interaction in an online forum -- 46 Active learning in Higher Education: A case study -- Part IV Networking & Collaboration -- 47 Establishing a Holistic approach for Postgraduate Supervision -- 48 Conceptualizing a framework in evaluating a collaboration model using technology for developing lesson contents -- Part V Other Areas -- 49 The relationship between Students' Malaysian Certificate of Education Forecast Results and Academic Performance in Business Studies at Pre-university -- 50 Final Year Engineering Project and its contribution to Holistic Education -- 51 Learning of Web Quality Evaluation: A case study of Malaysia National Museum Website using WebQEM Approach.
Keywords: Education; Education; Learning & Instruction; Electronic books